Peranan Dosen dalam Administrasi Pendidikan Tinggi terhadap Prestasi Belajar Bahasa Arab Mahasiswa - Iis Susiawati; Dadan Mardani; Muhammad Faiz Alhaq; Marjani Rahmah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Many factors support the success of an educational institution, including educational administration which is an important point, because it must be planned, organized, managed, monitored and evaluated properly. The important role of lecturers in determining the curriculum is part of higher education administration, including the Arabic language teaching curriculum. This paper aims to describe the role of Arabic lecturers in the administration of higher education and the Arabic language learning achievement of Arabic language education study program students. Based on data collection techniques whose sources are from the literature in the form of journal articles, books, modules, and other documents that support research data, this type of research is library research without any field research. Data were analyzed using inductive techniques, namely trying to find categories based on the data collected. So that the categories will appear after the data analysis process is carried out, then the data is presented descriptively. The results of this study are that there are several roles of lecturers in educational administration that are important in the development of student Arabic learning achievement, including lecturers acting as educators and teachers, facilitators, evaluators, managers, moral and character mentors, administrators, and also play a role in developing potential and student talent. It can be concluded that students are in a position as students who are taught, directed, guided, managed, motivated, facilitated, evaluated, and stimulated by their potential and talents so that they can become students who excel, are qualified, and are useful in their lives. Keywords: Lecturer, Education Administration, Learning Achievement, Student